Efikasi Diri (Self-Efficacy) Tokoh Masyarakat di Komunitas Adat Banceuy Subang - Theresia Martina Marwanti; Nenden Rainy Sundary; Hada Ma'ruf (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2026)
Traditional Kampong is identics as an area which permanently maintains value and tradition heritaged from ancestor. One of them is Banceuy Traditional Kampong. The purpose of the research is to describe how far of self-efficacy of key people in maintaining local wisdom in Banceuy Traditional Kampong. The research Aspects are level, strength and generality of key people in Bancuey Traditional Kampong Subang. The method used is quantitative method with descriptive approach. The population of it is 24 respondents so it is used census technique. Data gathering techniques are questionaire, observation and documentation. Validity test is biseral point corelation and pearson product moment. Reliability test is KR 20 alpha cronbach. The result shows on the three aspects level is high, the level aspect (62,5%), strength aspect (66,7%), andvgenerality (75,0%). Based on the three aspects can be concluded that self-efficacy of the key people is high (58,3%). Self-efficacy of they key people need to be more increased so higher self-efficacy, higher of self confidence of his compotencies to reach his goals. It shows that key people of Banceuy traditional kampong can be reliable as the one who has his own role and contribution to maintain local wisdom of Banceuy traditinal kampong.